Penerapan Model Pembelajaran Kooperatif Tipe Problem Based Learning untuk Meningkatkan Aktivitas dan Hasil Belajar Bahasa Indonesia Siswa Kelas VIII C SMP Negeri 1 Tanasitolo - Hj. Andi Ebe; Hj. Herniyastuti; Aulia Adhari; Nurcaya Nurcaya; Jumadi Jumadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2021)
Abstract: Application of Problem Based Learning Type Cooperative Learning Model to Improve Learning Activities and Outcomes Indonesian Class VIII C Students of SMP Negeri 1 Tanasitolo. The study aims to determine the improvement of Indonesian activities and learning outcomes through the application of a Problem Based Leaarning (PBL) type cooperative learning model for class VIII C students of SMP Negeri 1 Tanasitolo, Wajo Regency. The approach used in this study uses a qualitative approach with the type of class action research, the subject of this study is class VIII C students of SMP Negeri 1 Tanasitolo, Wajo Regency in the even semester of the 2018/2019 academic year totaling 21 students. This study was carried out in two cycles. Each cycle is held 3 times. The learning process of each meeting is designed using a Problem Based Learning (PBL) type cooperative learning model. At the end of cycle I, namely the third meeting and the end of cycle II, namely the sixth meeting, data collection was carried out using a learning outcomes test. The results showed that the increase in student learning activities increased from 54.16 to 84.42 and the average student learning outcome score increased from 65.71 to 87.14.